Novel biallelic mutations in the PNPT1 gene encoding a mitochondrial‐RNA‐import protein PNPase cause delayed myelination. Issue 2 (4th October 2017) - Sato, R.; Arai‐Ichinoi, N.; Kikuchi, A.; Matsuhashi, T.; Numata‐Uematsu, Y.; Uematsu, M.; Fujii, Y.; Murayama, K.; Ohtake, A.; Abe, T.; Kure, S.
Abstract : Recent studies suggest that impaired transcription or mitochondrial translation of small RNAs can cause abnormal myelination. A polynucleotide phosphorylase (PNPase) encoded by PNPT1 facilitates the import of small RNAs into mitochondria. PNPT1 mutations have been reported in patients with neurodevelopmental diseases with mitochondrial dysfunction. We report here 2 siblings with PNPT1 mutations who presented delayed myelination as well as mitochondrial dysfunction. We identified compound heterozygous mutations (c.227G>A; p.Gly76Asp and c.574C>T; p.Arg192*) in PNPT1 by quartet whole‐exome sequencing. Analyses of skin fibroblasts from the patient showed that PNPase expression was markedly decreased and that import of the small RNA RNaseP into mitochondria was impaired. Exogenous expression of wild‐type PNPT1, but not mutants, rescued ATP production in patient skin fibroblasts, suggesting the pathogenicity of the identified mutations. Our cases expand the phenotypic spectrum of PNPT1 mutations that can cause delayed myelination. Abstract :